Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1186/s13256-022-03366-y
|View full text |Cite
|
Sign up to set email alerts
|

A challenging case of an adolescent and young adult patient with high-risk acute lymphoblastic leukemia: the need for a multidisciplinary approach: a case report

Abstract: Background Adolescents and young adults diagnosed with acute lymphoblastic leukemia are treated according to pediatric-based regimens to achieve better results. However, implementation of intensive chemotherapy protocols in this age group is associated with increased treatment-related toxicities, affecting almost every organ and system. In this case, the focus of our interest was on rather rare entities: steroid-induced psychosis that seldom develops in children and adolescents, and choroid ple… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 32 publications
(36 reference statements)
0
4
0
Order By: Relevance
“…Ultimately, 24 studies met the eligibility criteria and were included in the review. 13,15,16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The current review revealed a variety of measures used to assess neurobehavioral side effects in the pediatric population undergoing corticosteroid treatment. Among the different methods of measurement identified in the included articles, clinical assessment and description was the most commonly used, utilized in seven articles.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations
“…Ultimately, 24 studies met the eligibility criteria and were included in the review. 13,15,16,[20][21][22][23][24][25][26][27][28][29][30][31][32][33][34][35][36][37][38][39] The current review revealed a variety of measures used to assess neurobehavioral side effects in the pediatric population undergoing corticosteroid treatment. Among the different methods of measurement identified in the included articles, clinical assessment and description was the most commonly used, utilized in seven articles.…”
Section: Resultsmentioning
confidence: 99%
“…Among the different methods of measurement identified in the included articles, clinical assessment and description was the most commonly used, utilized in seven articles. 15,16,30,[35][36][37][38] Sleep was evaluated by a combination of formalized measures, 13,20,29 actinography, 20,[24][25][26]32 sleep diaries, 21,25 and wearable technology (Micromini Motionlogger Sleep Watch). 24 Of the 12 validated scales identified (Table 1), the Pediatric Qualityof-Life Inventory (PedsQL) was most frequently used, utilized in four articles.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations